Pancreatic secretory response to intraileal amino acids: studies in dogs with an in situ neurally isolated ileum - Niebergall-Roth, Elke; Teyssen, Stephan; Niebel, Wolfgang; Singer, Manfred V. (International journal of gastrointestinal cancer, 2000)
Background: Intraileal carbohydrates and lipids affect the pancreatic exocrine secretion, but the effect of intraileal amino acids and the role of the extrinsic nerves of the ileum as mediators of the pancreatic bicarbonate and enzyme output are unknown.